2017
DOI: 10.1002/j.1681-4835.2017.tb00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Facing the Use of Mobile Applications for E‐Commerce in Kenya's Manufacturing Industry

Abstract: Ever-evolving wireless technology has given rise to a new way of conducting business, namely by using mobile devices that are ubiquitous and convenient to use in electronic commerce (e-commerce). Moreover, a new type of e-commerce has come into play, where business is conducted using applications installed on mobile devices -apps which can be tailored to perform specific services for each organisation. While the use of these apps has the capability of improving the profitability of an organisation, their uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The results of our work also concur with the findings of Mpogole et al (), which showed that the price of mobile phone use in Tanzania is more expensive than other East African countries. It is expensive in Tanzania and other Eastern Africa countries to manage mobile phone in terms of purchasing airtime (Kapinga et al, ), high cost of data bundles (Waithaka & Mnkandla, ). However, the costs of mobile phones and airtime are dropping rapidly because of the advances of technology and the blooming of telecommunication with several mobile phone service providers, and so it is expected that the smartphone will be commonplace in the very near future.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The results of our work also concur with the findings of Mpogole et al (), which showed that the price of mobile phone use in Tanzania is more expensive than other East African countries. It is expensive in Tanzania and other Eastern Africa countries to manage mobile phone in terms of purchasing airtime (Kapinga et al, ), high cost of data bundles (Waithaka & Mnkandla, ). However, the costs of mobile phones and airtime are dropping rapidly because of the advances of technology and the blooming of telecommunication with several mobile phone service providers, and so it is expected that the smartphone will be commonplace in the very near future.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…These categories become the critical determinants for the adoption of m-commerce. Waithaka and Mnkandla (2017), for example, employ the grounded theory for analyzing the interview data to explore the challenges facing the use of m-commerce in Kenyan SMEs in the manufacturing industry. The study finds that technological issues, security concerns, cost issues, environmental concerns, and computer literacy are the critical determinants for the use of m-commerce.…”
Section: Organizationsmentioning
confidence: 99%
“…Moreover, Chau et al ( 2020) and Fonseka and Jaharadak, 2022), assert that m-commerce can help organizations such as SMEs improve marketing processes by enhancing online payment systems (Fonseka & Jaharadak, 2022;Salimon & Kareem, 2021). According to (Maduku et al, 2016;Waithaka & Mnkandla, 2017;Matlakala, 2021), nowadays, most people no longer have much interest in buying things from the shop physically, but they prefer to purchase products from their homes or work offices using mobile applications. Matlakala (2021) indicates that the rate of mapplications utilization in South Africa is high, and the adoption of m-commerce will improve the performance of SMEs (Chau et al, 2020;Chau & Deng, 2018;Yahaya et al, 2022;Matlakala, 2021).…”
Section: Mobile Commerce (M-commerce)mentioning
confidence: 99%